Semiconductor substrate with n-doped intermediate layer

By epitaxially growing multi-layer Group 13 nitride on the starting substrate, filling the recessed areas of the material and using HVPE technology, the problems of high surface density, low crystal quality and uneven electronic characteristics of macroscopic inclusions in the prior art are solved, and a high-quality Group 13 nitride substrate and wafer are achieved.

CN113841260BActive Publication Date: 2025-02-28IV WORKS
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN201980091936.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-21
Filing Date
2019-12-18
Publication Date
2025-02-28
Estimated Expiration
2039-12-18

AI Technical Summary

Technical Problem

In the prior art, when manufacturing semiconductor material substrates and wafers based on Group 13 or III nitrides, there are problems such as high surface density of macroscopic inclusions, low crystal quality and uneven electronic characteristics, resulting in common failures in the manufacturing process of electronic and optoelectronic devices.

Method used

By epitaxially growing and deposition of multi-layer Group 13 nitride (such as GaN) on the starting substrate, the specific steps include depositing the first layer of GaN, supplying n-dopant gas to deposit the second layer of GaN, stopping the supply of dopant gas and epitaxially growing the third layer of GaN in the recessed area to fill the recessed area, using HVPE technology at a growth rate below 450 μm/h.

Benefits of technology

The low surface density of macroscopic inclusions is achieved, crystal quality is improved, and electronic characteristics is improved, ensuring the uniformity and efficiency of the wafer, with an average resistivity less than 25mohm.cm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113841260B_ABST
    Figure CN113841260B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a single crystal semiconductor material of a Group 13 nitride, comprising the following steps: a) depositing a first layer of a Group 13 nitride, preferably GaN, on a starting substrate by epitaxial growth, b) supplying an n-dopant gas and depositing a second layer of a Group 13 nitride, preferably GaN, on the first layer by epitaxial growth, said deposition comprising a material recessed area, c) stopping the supply of dopant gas and depositing a third layer of a Group 13 nitride, preferably GaN, on the previous doped layer by epitaxial growth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the general technical field of manufacturing substrates and wafers of semiconductor materials based on elements of Groups 13 and 15 of the Periodic Table of the Elements, such as gallium nitride (GaN).

[0002] These wafers are used to manufacture semiconductor structures such as light emitting diodes (LEDs), laser diodes (LDs), vertical transistors for power electronics, horizontal transistors for power electronics or telecommunications (radio frequency), current rectifier diodes or sensors. Background Art

[0003] Current processes for manufacturing semiconductor material substrates based on nitrides of group 13 or IIIA elements rely on vapor deposition techniques, in particular heteroepitaxy, which consists in growing a crystal (for example a gallium nitride GaN crystal) on a starting substrate of different properties (for example a sapphire substrate).

[0004] These methods involve injection systems from at least two different gaseous components that are able to interact prior to deposition.

[0005] Well-known methods may be mentioned, for example:

[0006] -Metal-organic vapor phase epitaxy (MOVPE),

[0007] - Hydride Vapor Phase Epitaxy (HVPE),

[0008] - Closed Space Vapor Transfer (CSVT) extension,

[0009] -Ceramic vapor deposition, etc.

[0010] So-called 3D growth processes or, for example, three-dimensional lateral growth allow the dislocation density to be reduced to less than 107 / cm 2 .

[0011] Under three-dimensional growth conditions, the HVPE growth front has a face perpendicular to the growth front and a face inclined to the growth front. Regarding the faces perpendicular to the growth front, these are faces formed by the basal plane (0001). It is well known that these faces contain less oxygen than the various inclined faces (non-basal planes, index hkil, where h≠0 and k≠0 and i≠0) that may exist. This difference in n-type doping causes some areas to be more resistant than other areas or to have different optical properties. After shaping, for example by correction and / or polishing, to obtain a two-dimensional surface, inhomogeneities in optical and / or electrical properties can be observed.

[0012] Furthermore, the lattice can have macroscopic inclusions with sizes larger than 10 μm, consisting mainly of twins, domain inversions or even polycrystals.

[0013] Furthermore, regardless of the process in 3D or 2D growth mode, the inevitable presence of defects or contamination on the starting substrate can lead to depressions in the material larger than 100 μm, known as pits. This type of defect, especially permanent voids or pits, has a decreasing cross-section in the direction opposite to the growth direction and increases in width and depth with increasing thickness of the deposit. These voids form large inverted pyramids hundreds of microns wide. At the apexes of these voids, the crystalline matrix can show crystal defects and high dislocation density.

[0014] All these defects generated during the growth process will lead to defects in the final wafer (doping heterogeneity and crystal defects, high dislocation density), which will cause failures during the manufacturing process of electronic and / or optoelectronic devices.

[0015] In order to improve the electronic properties of the substrate, for example, US2006255339A1 discloses a concentration of 0.7×10 18 About 3×10 18 / cm 3 At the same time, n-doped GaN crystals with a thermal conductivity of at least 1.5 W / cm.K are provided to enable devices, in particular diodes with a power exceeding 1 W. Even though only examples with Si doping are provided in this application, dopants such as Si, O, Ge, C, etc. may also be used alone or in combination.

[0016] US20110175200A1 proposes a HVPE growth process in which GeCl is added into the reaction chamber. 4 The crystals were doped with Ge to obtain more electronically conductive crystals to compensate for the sudden increase in resistivity observed when the growth rate was higher than 450 μm / h. However, such growth rates resulted in a high surface density of macroscopic inclusions and a lower crystal quality.

[0017] US9461121B2 claims a method for improving the distribution of n-dopants within a GaN crystal, typically by mixing Ga and dopant inputs for vapor phase growth. Uniform introduction into the reactor can be achieved by premixing the dopant and Ga before reacting with HCl or by mixing the dopant and gallium halide as a single conduit within the reaction chamber. The uniformity of the dopant concentration is measured by micro-Raman, microwave probe photoconductivity (MDP) or micro-photoluminescence. The uniformity level and method data indicate that this is clearly an HVPE process with 2D growth and therefore does not provide a solution for 3D growth processes.

[0018] There is therefore a need for Group 13 or Group III nitride materials, particularly substrates and wafers of Group 13 or Group III nitride materials, and more particularly wafers and substrates composed of GaN, which have a large thickness, typically greater than 100 microns, even 400 microns or more, more uniform and which simultaneously have:

[0019] - Low surface density of macroscopic inclusions, usually less than 5 cm -2 , preferably less than 4cm -2 , or even less than 1cm -2 ,

[0020] - Crystal quality, as measured by: the half-width at half-height of the X-ray diffraction (XRD) peak of the (002) line of the GaN (0001) plane under symmetric conditions near the angle ω, which is lower than 130 arc seconds, preferably lower than 100 arc seconds, more preferably lower than 90 arc seconds; and the half-width at half-height of the X-ray diffraction (XRD) peak of the 201 line of the GaN (0001) film under tilted conditions near the angle ω, which is lower than 240 arc seconds, preferably lower than 140 arc seconds, and

[0021] - Improved electronic properties, typically with an average resistivity of less than 25mohm.cm, or even less than 20mohm.cm. Summary of the invention

[0022] In this context, the object of the present invention is a method for producing a single-crystalline semiconductor material of a Group 13 nitride, comprising the following steps:

[0023] a) depositing a first layer of a Group 13 nitride, preferably GaN, on a starting substrate by epitaxial growth,

[0024] b) supplying an n-dopant gas and depositing a second layer of a Group 13 nitride, preferably GaN, on the first layer by epitaxial growth, said deposition comprising a material recessed region,

[0025] c) stopping the supply of dopant gas and depositing a third layer of Group 13 nitride (preferably GaN) by epitaxial growth on the previous doped layer and in the recessed areas of the second layer, so that the recessed areas of the second layer are filled by the deposition of the third layer.

[0026] As a note, unless otherwise stated, all chemical element concentrations mentioned herein are atomic concentrations.

[0027] Advantageously, but optionally, the method according to the invention may also include at least one of the following features:

[0028] The -n dopant gas contains at least one chemical element of Group 14 of the periodic table.

[0029] -The chemical element of Group 14 of the periodic table is: Germanium, which is obtained from solid sources, GeCl4 , germane, tetramethylgermane and isobutylgermane and their derivatives; and / or silicon, formed from a solid source, silane, dichlorosilane, silicon tetrachloride and their derivatives.

[0030] The n-dopant gas is mixed in the gas phase with the gallium chloride gas flow.

[0031] - Epitaxial growth is achieved by HVPE at a growth rate below 450 μm / h to ensure a low surface density of macroscopic inclusions and to ensure a satisfactory crystal quality.

[0032] - The epitaxial growth deposition step is performed by HVPE.

[0033] - A step of separating the starting substrate to obtain a free-standing Group 13 nitride single crystal semiconductor material.

[0034] - Fabrication of a self-supporting Group 13 nitride single crystal semiconductor material; said material comprising:

[0035] o a layer of a Group 13 nitride (preferably GaN) doped with an n-dopant to a predetermined thickness and having a material recessed region;

[0036] o an undoped Group 13 nitride (preferably GaN) layer disposed on the doped layer and in the material recessed region of the doped layer;

[0037] o Correction is made by removal to obtain an n-doped layer according to a given thickness to form a Group 13 or Group III nitride wafer.

[0038] - Wafer selection step, including the following sub-steps:

[0039] o performing Raman spectroscopy to identify less doped or undoped regions of the wafer, referred to as minimum doped regions;

[0040] ο Identify non-radiative defects by cathodoluminescence to select those with a maximum threading dislocation density or TDD greater than 1×10 8 cm -2 The wafer is confined to an area within a circle of 50 μm in diameter, the center of which coincides with the center of each minimum doped region.

[0041] Another object of the present invention is a Group 13 nitride single crystal semiconductor material comprising:

[0042] - a first layer of a Group 13 nitride, preferably GaN, having permanent defect regions corresponding to voids or pits of decreasing cross-section in a direction opposite to the growth direction;

[0043] - a second layer of a Group 13 nitride (preferably GaN) doped with an n-dopant to a predetermined thickness and having a material recessed region coinciding with a permanent defect region in the first layer or a defect region formed in the second layer;

[0044] - a third layer of undoped Group 13 nitride, preferably GaN, arranged on the doped layer and in the material recessed regions of the doped layer, the recessed regions of the second layer being filled by the deposition of the third layer.

[0045] Advantageously, but optionally, the single-crystalline semiconductor material according to the present invention may also include at least one of the following features:

[0046] - the thickness of the second n-doped layer is between 100 and 2000 micrometers:

[0047] - The thickness of the first layer is between 100 and 1000 microns:

[0048] - the thickness of the third layer is between 200 and 5000 microns;

[0049] - the ratio of the thickness of the second layer to the thickness of the first layer is between 0.1 and 20;

[0050] - The n-dopant content of the second layer is greater than 1×10 18 cm -3 and less than 2×10 19 cm -3 .

[0051] Another object of the present invention is a Group 13 or Group III nitride wafer that can be manufactured according to the above method and comprises:

[0052] - a layer of a Group 13 nitride, preferably GaN, doped with an n-dopant and having a material recessed region;

[0053] - an undoped Group 13 nitride (preferably GaN) layer disposed in the material recessed region of the doped layer;

[0054] The top surface of the wafer includes:

[0055] - a first doped region, corresponding to the upper surface of the doped layer, having a free carrier density greater than 1.0×10 18 cm -3 ;and

[0056] a less doped or undoped second region corresponding to the upper surface of the undoped layer arranged in a material recess of the doped layer, the free carrier density of the second region being less than 8×10 17 cm -3 , preferably less than 5×10 17 cm-3 .

[0057] Advantageously, but optionally, a Group 13 or Group III wafer according to the present invention may also include at least one of the following features:

[0058] - The first doped region includes a chemical element of Group 14 of the periodic table, which is germanium, obtained from a solid source, GeCl 4 , germane, tetramethylgermane and isobutylgermane and their derivatives; and / or silicon, formed from a solid source, silane, dichlorosilane, silicon tetrachloride and their derivatives.

[0059] - The dopant content of the first region is greater than 1×10 18 cm -3 and less than 2×10 19 cm -3 .

[0060] - The oxygen concentration of the first doping region is less than 2.0×10 18 cm -3 .

[0061] - by controlling the purity of the Group III precursor and by subjecting the reactor to one or more very thorough purges at a residual pressure of less than 10 Torr, followed by one or more N 2 Purge to control oxygen supply and concentration.

[0062] - The cumulative concentration of oxygen atoms and n-dopants in the crystal is less than 1.0×10 19 cm -3 .

[0063] The area of ​​the second region is less than 5%, or even less than 2%, of the area of ​​the wafer.

[0064] - Crystal quality, measured by: the half-width at half-height of the X-ray diffraction (XRD) peak of the (002) line of the GaN (0001) plane under symmetric conditions near the angle ω, which is lower than 130 arc seconds, preferably lower than 100 arc seconds, more preferably lower than 90 arc seconds, or even lower than 60 arc seconds; and the half-width at half-height of the X-ray diffraction (XRD) peak of the 201 line of the GaN (0001) film under tilted conditions near the angle ω, which is lower than 240 arc seconds, preferably lower than 140 arc seconds, or even lower than 100 arc seconds.

[0065] -The average resistivity of the wafer is less than 25mohm.cm.

[0066] Another object of the invention is the use of a Group 13 or Group III nitride wafer according to one of the preceding features as a substrate for the manufacture of electronic and / or optoelectronic components, such as light-emitting diodes, laser diodes, vertical transistors for power electronics, horizontal transistors for power electronics or telecommunications (radio frequency), current rectifier diodes or sensors.

[0067] The invention also relates to a method for selecting defective regions within a wafer of a Group 13 nitride single-crystal semiconductor material, said defective regions causing defects in optoelectronic components arranged on or near these regions.

[0068] More specifically, another object of the present invention is a method for selecting defect areas within a wafer of a Group 13 nitride single crystal semiconductor material before or after deposition of a photovoltaic element, comprising the following steps:

[0069] - according to a first step, Raman spectroscopy is performed to identify less doped or undoped areas of the wafer, called minimum doped areas,

[0070] or by photoluminescence, preferably by cathodoluminescence, to identify a maximum threading dislocation density (TDD) higher than 1x10 8 cm -2 Non-radiative defects,

[0071] - According to a second step, an area is selected which is inscribed in a circle of 50 μm in diameter, the center of which coincides with the center of each minimum doping area corresponding to an area where a defect of the optoelectronic element may be present, so as to

[0072] Prior to depositing the optoelectronic components on the wafer, avoid deposition within this selected 50 μm diameter region, and / or

[0073] After deposition of the optoelectronic components on the wafer, the components deposited in this selected 50 μm diameter area are removed. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] Other characteristics, objectives and advantages of the invention will emerge on reading the following detailed description and with reference to the accompanying drawings, given by way of non-limiting examples, in which:

[0075] [ Figure 1 ]

[0076] - Figure 1 Main steps of a substrate manufacturing method according to one embodiment of the present invention are summarized.

[0077] [ Figure 2 ]

[0078] - Figure 2 A semiconductor material consisting of a multilayer stack according to a possible embodiment of the present invention is schematically shown.

[0079] [ Figure 3 ]

[0080] - Figure 3 It is illustrated that a slice of free-standing GaN material according to a possible embodiment of the present invention comprises, after separation, an undoped first or lower layer, an n-doped second or lower or intermediate layer, and an undoped third or upper layer.

[0081] [ Figure 4 ]

[0082] - Figure 4 Represents a cross section of a wafer after slicing of the corrected and finished support material.

[0083] [ Figure 5 ]

[0084] Figure 5 Respectively represent the Raman spectra measured at the bottom of the growth pit and its surroundings. DETAILED DESCRIPTION

[0085] refer to Figure 1 , 2 , illustrating the main stages of the GaN wafer manufacturing method.

[0086] In the following, the process according to the invention will be described with reference to the manufacture of silicon nitride GaN wafers.

[0087] However, it will be apparent to those skilled in the art that the process described below may be used to grow materials including Group 13 nitride layers other than gallium nitride GaN.

[0088] 1. Manufacturing method

[0089] The process includes:

[0090] - Growth stage 10 of a first layer 5a of a Group 13 nitride, preferably GaN;

[0091] - stage 20 of forming the separation zone 4;

[0092] - stage 30 of resuming epitaxy to form a thick undoped GaN layer 5 b , a thick n-doped GaN layer 5 c and finally a thick undoped GaN layer 5 d ;

[0093] - a separation stage 40 to obtain GaN crystals 5;

[0094] - a correction phase 45 to remove the thickness of the thick undoped GaN layer;

[0095] A finishing phase 50 to form a GaN wafer from the GaN crystal 5 .

[0096] 1.1 Growth stage 10

[0097] The optional growth phase 10 comprises forming a GaN sublayer 5a by lateral overgrowth.

[0098] The lateral overgrowth minimizes the defect density contained in the GaN sublayer 5a.

[0099] Methods for reducing the dislocation density in the GaN sublayer 5a include:

[0100] - Start the island mode of GaN growth, and then

[0101] - Promote the coalescence of islands to obtain a GaN sublayer 5a.

[0102] Advantageously, the lateral overgrowth is achieved on a starting substrate 1 having a non-zero cut-off angle.

[0103] Using a starting substrate 1 with a non-zero cutoff angle allows growing a first GaN layer 5a with a non-zero cutoff angle.

[0104] The starting substrate 1 can be selected from Si, AlN, GaN, GaAs, Al 2 O 3 (Sapphire), ZnO, SiC, LiAlO 2 、LiGaO 2 MgAl 2 O 4 , 4H-SiC, or any other type of starting substrate known to a skilled person for achieving gallium nitride growth.

[0105] It may have a thickness of several hundred microns, typically 350 microns.

[0106] Advantageously, the starting substrate 1 may be treated by nitridation before any deposition step. This improves the quality of the GaN crystal obtained.

[0107] The cut-off angle may be comprised between 0.1 and 5 degrees, preferably between 0.2 and 0.8 degrees, even more preferably between 0.3 and 0.6 degrees (particularly in order to limit stacking errors).

[0108] The growth of the GaN sublayer 5a can be achieved in different variants. In particular, the lateral overgrowth can be based on:

[0109] - using a dielectric mask 3 b comprising openings 3 a in which islands are formed, as described in document WO 99 / 20816;

[0110] - Use of a dielectric layer without openings on which islands are formed spontaneously, as described in document EP 1 338 683.

[0111] 1.2.1. The first variant of lateral overgrowth

[0112] In a first variant, the growth stage 10 is an epitaxial lateral overgrowth (hereinafter referred to as ELO).

[0113] ELO comprises the step of depositing a thicker planarization layer 2 on a starting substrate 1 .

[0114] The deposition is preferably performed by metal organic vapor phase epitaxy (MOVPE), for example at a temperature comprised between 500°C and 700°C, in particular at 600°C.

[0115] The deposition of layer 2 reduces the stress between the starting substrate 1 and the subsequently epitaxial GaN sublayer 5a. In fact, the deposition of layer 2 on substrate 1 ensures a "soft" transition between substrate 1 and GaN sublayer 5a (whose crystal structures are different).

[0116] The deposition of layer 2 further facilitates the subsequent separation of GaN crystals 5, as will become apparent from the following description. Layer 2 is, for example, a GaN layer, an AlN layer or an AlGaN layer.

[0117] In a further step, a mask 3b is formed comprising openings 3a. The openings 3a may be in the form of dots or stripes and define locations for the subsequent selective growth of GaN islands.

[0118] The mask 3b may be made of a dielectric material (eg SiN x (SiN, Si 3 N 4 etc.) or SiO 2 This minimizes defects at the mask edge, thereby improving the quality of the GaN layer that is subsequently grown on it.

[0119] The formation of the mask 3b may be performed by any technique known to those skilled in the art. For example, the formation of the mask may include:

[0120] Deposition of dielectric layer 3a directly on layer 2 from gaseous silane and ammonia precursors, and

[0121] The dielectric layer 3a is etched by photolithography to form an opening 3a.

[0122] A starting substrate 1 covered with layer 2 and mask 3b is thus obtained. Besides improving the quality of GaN sublayer 5a (by filtering out defects), mask 3b also weakens the interface between starting substrate 1 and GaN sublayer 5a.

[0123] Another step consists in forming GaN islands through the mask openings 3a. The growth rate along the axis orthogonal to the main plane of the starting substrate 1 is kept higher than the lateral growth rate. This results in islands or strips (depending on the shape of the openings 3a) with a triangular cross section. In these strips with a triangular cross section, the threading dislocations are bent by 90°.

[0124] Lateral overgrowth then takes place to finally form a planar ELO layer. At the end of this process step, a dislocation density of less than 10 8 cm -2 The first GaN layer 5a.

[0125] 1.2.2. Second variant of lateral overgrowth

[0126] In a second variant, the growth stage 10 consists of a universal lateral overgrowth (hereinafter referred to as ULO) as described in document EP 1 977 028 .

[0127] ULO comprises the step of depositing a nucleation layer on a starting substrate 1 .

[0128] The nucleation layer is, for example, a very thin silicon nitride SiN film of about a few atomic planes, ie about 10 nm to 20 nm thick. The silane and ammonia based SiN deposition may last for 360 seconds.

[0129] A continuous buffer layer 2 (eg GaN) is then deposited on the nucleation layer. The deposition of the GaN buffer layer 2 filters out crystal defects and thus minimizes the defect density that will be present in the subsequently epitaxial first GaN sublayer 5a from the beginning of the process.

[0130] The thickness of the GaN buffer layer 2 may be between 10 and 100 nm. The temperature during the operation may be between 500 and 700°C.

[0131] Annealing is then performed at an elevated temperature of 900 to 1150°C. Under the combined effect of the elevated temperature, the presence of a sufficient amount of hydrogen in the carrier gas and the presence of a very thin SiN film, the morphology of the GaN buffer layer 2 undergoes a deep change due to solid phase recrystallization caused by mass transfer. The initially continuous GaN buffer layer 2 is then transformed into a discontinuous GaN pattern layer. Due to the very small thickness of the nucleation layer, a GaN pattern or island is obtained that has very good crystalline quality and maintains an epitaxial relationship with the starting substrate.

[0132] The exposed areas of silicon nitride SiN are then used as a mask, and the GaN pattern is used as the GaN regions located in the openings made ex situ in the mask. Lateral overgrowth is then performed to ultimately form a planar ULO layer.

[0133] This method, in which the silicon nitride mask forms spontaneously, and involves the same dislocation bending mechanism as in ELO, is identified as "ULO" (or "spontaneous ELO").

[0134] 1.2 Stage 20 of forming separation zone 4

[0135] The process also comprises a stage 20 of forming the separation zone 4 .

[0136] This stage 20 of forming the separation zone can be implemented according to different variants. In particular, the stage 20 of forming the separation zone can be implemented:

[0137] - before the growth stage 10 of the first GaN layer (first variant), or

[0138] - after the growth phase 10 of the first GaN layer (second variant), or

[0139] - During the growth phase 10 of the first GaN layer (third variant).

[0140] 1.2.1. First variant of forming separation zone 4

[0141] In a first variant, the step 20 of forming the separation zone 4 may consist in depositing a sacrificial intermediate layer before the growth stage 10 of the GaN sublayer 5 a , as described in document EP 1 699 951 .

[0142] The intermediate layer, which may be Si, ZnO, TiN, SiN, TiC, serves as a sacrificial layer that evaporates spontaneously during the subsequent epitaxial growth phase of the GaN sublayer 5a.

[0143] 1.2.2. Second variant of forming the separation zone

[0144] In a second variant, the stage 20 of forming the separation zone 4 comprises an implantation step carried out after the growth stage 10 of the GaN sublayer 5a. This implantation allows the creation of an embrittled zone in the GaN sublayer 5a.

[0145] The implantation consists in bombarding the GaN sublayer 5a with ions to create a layer of microcavities (or bubbles) in the semiconductor at a depth close to the average penetration depth of these ions.

[0146] The implanted ions may be selected from tungsten, helium, neon, krypton, chromium, molybdenum, iron, hydrogen or boron. Preferably, the implanted ions are tungsten ions. They have a special feature of decomposing GaN.

[0147] In terms of dosage, when the implanted ions are H+ ions, the implanted ion dosage can be between 10+ and 10 17 cm -2The implantation depth may vary between 0 nm and 50 nm starting from the free surface of the first GaN sublayer 5a, called the growth face.

[0148] The implantation of embrittlement ions can be carried out in a single step or in a series of steps. During the implantation step, the temperature can be between 4K and 1400K.

[0149] The implantation may be followed by an annealing phase to cure the crystal damage produced during the ion implantation, which annealing may be performed at a temperature comprised between 500°C and 1500°C.

[0150] 1.2.3. Third variant of forming the separation zone

[0151] In a third variant, the separation zone 4 may be formed during the growth phase 10 of the GaN sublayer 5a.

[0152] In particular, when the growth phase is carried out according to the first variant embodiment called ELO (ie the deposition of the dielectric mask 3 b ), the phase 20 of forming the separation zone 4 may comprise the implantation of the buffer layer 2 before the deposition of the mask 3 b .

[0153] This allows the separation zone 4 to be placed at the exact desired depth, since the first GaN layer 5a deposited in the ELO step does not "interfere" with the ion implantation.

[0154] Of course, the implantation can be performed at different stages of the ELO (or ULO) phase, either within the island, at an intermediate stage when the island is not fully coalesced, or after the island is fully coalesced.

[0155] 1.3 Epitaxial recovery stage 30

[0156] At the end of the phase 20 of forming the separation zone 4 and the growth phase 10 of the GaN sublayer 5a, the process comprises an epitaxial recovery phase 30 to form a thick first undoped GaN layer 5b, a thick second n-doped GaN layer 5c and a thick third undoped GaN layer 5d.

[0157] The process can also start directly at this stage 30 by forming a thick GaN layer 5b, the growth stage 10 and the stage 20 of forming the separation zone being optional. In the following, the application of these stages 10 and 20 is considered.

[0158] This epitaxial recovery can be achieved by:

[0159] -Metal-organic vapor phase epitaxy (MOVPE);

[0160] -Hydride vapor phase epitaxy (HVPE);

[0161] - Closed Space Vapour Transfer (CSVT) extension; or

[0162] -Liquid Phase Epitaxy (LPE).

[0163] In this step, HVPE technology is preferably used, which can achieve three main beneficial effects:

[0164] - The first effect is that the GaN sublayer 5a is thickened without losing its crystalline quality (without generating new dislocations or cracks);

[0165] - A second effect is that the dislocation density is further reduced by at least a factor of 2 during HVPE over 100 μm of GaN growth (0001) (ref. https: / / doi.org / 10.1143 / APEX.5.095503);

[0166] A third effect is that the thick GaN layer 5 thus obtained may, in certain cases, allow spontaneous detachment from its starting substrate 1 at the detachment zone 4 in the event of sublimation or mechanical fracture of said detachment zone during HVPE growth.

[0167] More precisely, the recovery is carried out according to the following process: the temperature is increased in a nitrogen and a mixed atmosphere of ammonia and hydrogen. Once a stable temperature of about 1000°C is reached, the growth phase of the thick GaN layer is then initiated by introducing a gas phase such as gallium chloride (GaCl). GaCl and ammonia are partially pyrolyzed in a growth chamber maintained at a temperature of about 1000°C. Thus, a single-crystalline GaN deposit is gradually formed at the level of the nucleation substrate (formed during the first growth phase).

[0168] It is necessary to obtain a GaN layer that is thick enough and therefore resistant enough from a mechanical point of view, to avoid the GaN layer from breaking into small pieces during the separation process and to facilitate its handling without the risk of breaking. Under these experimental conditions, the growth lasts for several hours to achieve a GaN layer of at least 200 microns thickness, preferably a thickness greater than 1 millimeter.

[0169] The growth is then finalized by diverting the HCl flow to the outside, and cooling is performed in an atmosphere consisting of nitrogen and ammonia.

[0170] The growth conditions of these first, second and third single crystal layers 5b, 5c, 5d are generally a growth temperature between 900 and 1200°C, and a growth rate between 50 and 500 microns / hour, preferably between 70 and 200 microns / hour.

[0171] The thickness of the original self-supporting GaN crystal thus obtained is greater than 200 micrometers, preferably greater than 1 mm, and its maximum thickness is less than 10 mm, or even less than 5 mm.

[0172] The original self-supporting GaN crystal thus obtained has a diameter greater than 50 mm, preferably greater than 100 mm, and its maximum diameter is less than 250 mm, or even less than 200 mm.

[0173] refer to Figure 3 , layer 5b has permanent defect areas, corresponding to voids or pits whose cross-section decreases in a direction opposite to the growth direction.

[0174] In the second step, under the same growth conditions, a second single crystal GaN layer 5c is obtained on the layer 5b by adding an n-doping element for doping according to the following method:

[0175] - Controlling the oxygen supply and concentration by controlling the purity of the Group III precursor and by performing a very thorough purge of the reactor prior to growth under vacuum at a residual pressure below 500 Torr.

[0176] -For Germanium: from solid sources, GeCl 4 , germane, tetramethylgermane and isobutylgermane and their derivatives. These dopant gases are then evaporated in the reaction chamber. Preferably, these dopant gases can be pre-mixed with the GaCl flow in the gas phase to improve the uniform distribution of the doping flow in the growth chamber.

[0177] - In the case of a gaseous precursor, the gas tank is maintained at a pressure between 1 bar and 3 bar and a carrier gas (N) with a flow rate between 0.25 sccm and 20 sccm is applied. 2 and / or H 2 )flow.

[0178] - For silicon, from silane, dichlorosilane, silicon tetrachloride and their derivatives evaporated in the reaction chamber. In dichlorosilane (1%, diluted in 99% N 2 (or H 2 ) in the case of ), a flow rate between 1 and 20 sccm is applied. Preferably, these dopant gases can be mixed with the GaCl flow in the gas phase to improve the uniform distribution of the doping flow in the growth chamber.

[0179] - Silicon and germanium can be introduced together to form a 3-dopant system.

[0180] Typically, the thickness of the first single crystal GaN layer 5b is 100 to 1000 micrometers.

[0181] The permanent defect regions 6 of the layer 5b cause the defects to propagate also into the layer 5b. Thus, during the growth of the second doped layer 5c, a material depression of the layer 5c is obtained in the depression region coinciding with the defect region of the layer 5b.

[0182] Other forms of material depression may appear to be related to inclusions or nucleations which locally modify the growth rate without reaching the upper surface of layer 5b or even 5c.

[0183] In a third step, the supply of the n-dopant gas is stopped and the growth conditions are maintained, thereby obtaining a third single-crystal GaN layer 5d having a typical thickness of 200 to 5000 micrometers on the previous doped layer 5c having a typical thickness of 100 to 2000 micrometers.

[0184] The obtained single-crystalline layer thickness and the growth mode of GaN 5d allow filling the recessed areas of layer 5c by depositing this third layer.

[0185] 1.4 Separation stage 40

[0186] A separation stage 40 is also implemented, which depends on the variant implemented for the stage 20 of forming the separation zone 4 .

[0187] In the case of ion implantation, a spontaneous separation phase 40 occurs due to the thermal cycle (high temperature epitaxial recovery and cooling) experienced by the thickened GaN layer 5, causing stress due to the difference in thermal expansion coefficients between the starting substrate 1 and the thickened GaN layer 5, leading to their separation.

[0188] In the case of deposited sacrificial intermediate layers, this separation takes place during the epitaxial process by spontaneous evaporation of the intermediate layer or by mechanical fracture at the level of the so-called sacrificial layer.

[0189] In the case of post-growth separation, a laser can be used to evaporate the sacrificial layer.

[0190] Get as Figure 3 The free-standing GaN crystal 5 is shown.

[0191] This crystal, such as Figure 3 (non-curved representation) as shown, it can be curved and have a radius of curvature that is generally greater than 5 meters and less than 25 meters, preferably less than 20 meters. In addition, the crystal 5 also has 10 7 cm -2 or less, preferably less than 5×10 6 cm -2 The dislocation density.

[0192] The GaN crystal 5 that has been formed on a starting substrate having a non-zero cut-off angle (or air cut) also has a non-zero cut-off angle, wherein the orientation of the crystal plane propagates from one layer to the next. For example, in the case of a sapphire substrate 1 having a cut-off angle of 4 degrees, the growth face of the crystal 5 has a cut-off angle of 4 degrees, preferably between 0.1 and 1 degrees, over its entire surface.

[0193] 1.5 Correction stage 45

[0194] Once the GaN crystal 5 is separated from the starting substrate 1, it is rectified.

[0195] Current technology allows controlled removal of layer thicknesses within 10 microns.

[0196] 1.6 Finishing stage 50

[0197] A finishing operation is then performed to form a GaN wafer whose GaN thin film (0001) has a half-height width of an X-ray diffraction (XRD) peak of a (002) line near an angle ω under symmetric conditions of less than 130 arc seconds or even less than 90 arc seconds, preferably less than 60 arc seconds.

[0198] The back and sides or edges of the wafer are straightened and polished to a surface finish acceptable for the application.

[0199] Correction is performed by removing the thickness corresponding to the second n-doped layer 5c, such as Figure 3 As shown, to form a Group 13 or Group III nitride wafer.

[0200] Therefore, the proposed process is particularly suitable for manufacturing slices or wafers of semiconductor materials, in particular slices or wafers of materials of elements of Groups 13 and 15 of the periodic table, more particularly slices or wafers consisting of large diameter Group 13 nitrides, preferably GaN, the large size being greater than 5 cm, more than 10 cm or even 15 to 20 cm.

[0201] refer to Figure 4 , a slice or wafer of semiconductor material 7 formed according to the method of the present invention has:

[0202] - an n-doped region of smaller value. It coincides with the high-density crystal defect region in such a way that, in a plane perpendicular to the growth direction, the gallium face comprises a first n-doped region 7a whose free carrier density measured by the van der Pauw method is greater than 1.0×10 18 cm -3 , and an undoped or less n-doped second region 7b corresponding to a material depression, for example coinciding with a permanent defect of the first layer, for example a growth pit, wherein the free carrier density of the second region measured by the Hall effect is less than 1.0×10 18 cm -3 ,and

[0203] -Thickness of about 450 microns and

[0204] - excellent crystal quality, such that the half-width of the X-ray diffraction (XRD) peak of the (002) line near the angle ω under symmetric conditions of the (0001) GaN film is less than 130 arc seconds or even less than 60 arc seconds, and

[0205] -The surface density of macroscopic inclusions is less than 5cm -2 , preferably less than 1cm -2

[0206] - Average resistivity less than 25mohm.cm.

[0207] 1.7 Selection stage 60

[0208] The proposed method may also include a wafer selection phase, including the following sub-steps:

[0209] -Perform Raman spectroscopy, reference Figure 5 , to identify less doped or undoped areas of the wafer, called minimum doping regions, which are located around the permanent defect areas.

[0210] The measurements were performed on a Thermo DXRxi Raman spectrometer. This spectrometer is dedicated to fast Raman imaging and has a maximum acquisition capacity of 600 spectra / second. In one configuration, a 532nm laser with 10mW power was used for analysis. The laser beam was focused on the sample through a microscope that provided 50x magnification;

[0211] - Identification of non-radiative defects by cathodoluminescence to select those with a maximum threading dislocation density or TDD greater than 1×10 8 cm -2 The wafer is confined to an area within a circle of 50 μm in diameter, the center of which coincides with the center of each minimum doped region.

[0212] This identification makes it possible to select an area inscribed in a disk with a diameter of 50 μm, the center of which coincides with the center of each minimum doping area, corresponding to the area where defects in the optoelectronic element may be present, in order to avoid such deposition in this selected 50 μm diameter area before depositing the optoelectronic element on the wafer, and / or to remove components deposited in this selected 50 μm diameter area after depositing the optoelectronic element on the wafer.

[0213] According to another possible process, by way of illustration and in comparison with the process described above, the single-crystalline material according to the invention is obtained by growth on a starting substrate or seed (for example sapphire) on which preferably a GaN nitride layer, preferably at least a few microns and less than 10 microns, has been previously deposited. The growth is carried out in a HVPE type reactor. The epitaxial deposition is carried out under the same conditions as in stage 30 above, but for a longer time in order to form a layer of a few millimeters.

[0214] The crystal undergoes a trimming operation and is then cut into several slices or wafers, typically 100 to 600 microns thick, using either a loose wire saw (abrasive grains in a slurry that impregnates the wire before cutting) or a fixed wire saw (abrasive grains pre-fixed on the wire). The finishing steps (pre-polishing, polishing) are similar to the above process.

Claims

1. A method for manufacturing a Group 13 nitride wafer, comprising the steps of: a) depositing a first layer of a Group 13 nitride on a starting substrate by epitaxial growth, b) supplying an n-dopant gas and depositing a second layer of a Group 13 nitride on the first layer by epitaxial growth, said depositing of a second layer comprises a recessed region of material, c) stopping the supply of dopant gas and depositing a third layer of Group 13 nitride by epitaxial growth on the previous doped layer and in the recessed region of the second layer, so that the recessed region of the second layer is filled by the deposition of the third layer, d) separating the starting substrate to obtain a free-standing Group 13 nitride single crystal semiconductor material, The self-supporting Group 13 nitride single crystal semiconductor material comprises: a Group 13 nitride layer doped with an n-dopant to a predetermined thickness and having a material recessed region; and an undoped Group 13 nitride layer disposed on the n-doped layer and in a material recessed region of the n-doped layer; e) correcting by removal to obtain an n-doped layer according to a given thickness to form a Group 13 nitride wafer, f) Selecting a wafer, comprising the following sub-steps: performing Raman spectroscopy to identify less doped or undoped regions of the wafer, referred to as minimum doped regions; Non-radiative defects were identified by cathodoluminescence to select those with a maximum threading dislocation density or TDD greater than 1 × 10 8 cm -2 The wafer is confined to an area within a circle of 20 μm in diameter, the center of which coincides with the center of each minimum doped region. 2 . The manufacturing method according to claim 1 , wherein the n-dopant gas contains at least one chemical element of Group 14 of the periodic table.

3. The manufacturing method according to claim 2, wherein the chemical element of Group 14 of the periodic table is: germanium, formed from a solid source, GeCl4, germanium, tetramethylgermanium and isobutylgermane and derivatives thereof; and / or, Silicon, formed from solid sources, silane, dichlorosilane, silicon tetrachloride, and their derivatives. 4 . The method of claim 1 , wherein the n-dopant gas is mixed in the gas phase with the gallium chloride gas flow. The manufacturing method according to claim 1 , wherein the epitaxial growth deposition step is performed by HVPE.

6. The manufacturing method according to claim 1, wherein the thickness of the second layer is between 100 and 2000 microns.

7. The manufacturing method according to claim 1, wherein the thickness of the first layer is between 100 and 1000 microns.

8. The manufacturing method according to claim 1, wherein the thickness of the third layer is between 200 and 5000 microns. 9 . The manufacturing method according to claim 1 , wherein a ratio of a thickness of the second layer to a thickness of the first layer is between 0.1 and 20.

10. The manufacturing method according to claim 1, wherein the n-dopant content of the second layer is greater than 1×10 18 cm -3 and less than 2×10 19 cm -3 .

11. A Group 13 nitride wafer manufactured according to the method of claim 1 and comprising: a Group 13 nitride layer doped with an n-dopant and having a material recessed region; an undoped Group 13 nitride layer disposed in a material recessed region of the doped layer; The upper surface of the wafer comprises: The first doped region, which corresponds to the upper surface of the doped layer, has a free carrier density greater than 1.0×10 18 cm -3 ;and A less doped or undoped second region corresponding to the upper surface of the undoped layer arranged in a material recessed region of the doped layer, the free carrier density of the second region being less than 8×10 17 cm -3 .

12. The Group 13 nitride wafer of claim 11, wherein the first doped region comprises a chemical element of Group 14 of the periodic table, the chemical element of Group 14 of the periodic table being germanium and formed from a solid source, GeCl4, germanium, tetramethylgermanium and isobutylgermane and derivatives thereof; and / or Silicon, formed from solid sources, silane, dichlorosilane, silicon tetrachloride, and their derivatives.

13. The Group 13 nitride wafer according to any one of claims 11 to 12, wherein the dopant content of the first doped region is greater than 1×10 18 cm -3 and less than 2×10 19 cm -3 .

14. The Group 13 nitride wafer according to claim 11, wherein the oxygen O concentration of the first doped region is less than 2.0×10 18 cm -3 .

15. The Group 13 nitride wafer according to claim 14, wherein the cumulative concentration of oxygen (O) atoms and n-dopants in the wafer is less than 1.0×10 19 cm -3 .

16. The Group 13 nitride wafer of claim 11, wherein the area of ​​the second region is less than 5% of the area of ​​the wafer.

17. The Group 13 nitride wafer of claim 11, wherein the area of ​​the second region is less than 2% of the area of ​​the wafer.

18. The Group 13 nitride wafer of claim 11, wherein the nitride is GaN, and the wafer quality is measured by: a half-width at half-maximum of an X-ray diffraction (XRD) peak of a (002) line of a GaN plane (0001) near an angle ω under symmetric conditions, which is less than 130 arc seconds; and a half-width at half-maximum of an X-ray diffraction (XRD) peak of a 201 line of a GaN film (0001) near an angle ω under tilted conditions, which is less than 240 arc seconds.

19. The Group 13 nitride wafer of claim 11, wherein the wafer has an average resistivity of less than 25 mohm.cm.

20. Use of the Group 13 nitride wafer according to claim 11 as a substrate for the manufacture of optoelectronic components, including light emitting diodes, laser diodes, vertical transistors for power electronics, horizontal transistors for power electronics or telecommunications, current rectifier diodes or sensors.

Citation Information

Patent Citations

  • Process for making an epitaxial layer of gallium nitride

    EP1338683A2

  • Method of producing self-supporting substrates comprising iii-nitrides by means of heteroepitaxy on a sacrificial layer

    EP1699951A2

  • Process for growth of low dislocation density GAN

    EP1977028A1

  • Single-crystalline gallium nitride substrate

    US20060255339A1

  • Manufacturing method of conductive group iii nitride crystal, manufacturing method of conductive group iii nitride substrate and conductive group iii nitride substrate

    US20110175200A1